TANTANGAN DAN PELUANG PENEGAKAN HUKUM DALAM PEMBERANTASAN TINDAK PIDANA KORUPSI - Martini, Martini (Solusi, 2019)
The challenges of law enforcement in eradicating corruption are among others: the lack of trust in law enforcement officers; Examination of corruption cases in court by judges prioritizes the fulfillment of formal legal actions. The absence of a judge's decision which is a symbol of firmness in combating corruption: awareness of the impact of corruption is still too abstract and poorly understood by the community; The war on corruption is still merely a political discourse or entertainment for the people; the absence or lack of opportunities to participate in eradicating corruption is the reason why people do not care or are concerned about eradicating corruption. Besides the inherent habit that bahwa if all want to be fast, money is the solution ’and culture that is‘ nrimo ’or does not want to question all matters related to the administration of the state, as if it is an element of fertilization. Opportunities for law enforcement in eradicating corruption include: Issuance of Law No. 31 of 1999 concerning Eradication of Corruption Crime; the growth of the Corruption Perception Index (CPI) in Indonesia is the highest compared to other countries in the world; national concerns about corruption can stimulate governments and anti-corruption activists to campaign extensively with high intensity; The press has become a powerful media for raising public awareness of the effects of corruption